Comparison of Milk Yield of Cows of the Holshtin Breed to the Standard Template of the Breed (Czech Journal of Multidisciplinary Innovations, 2022)
In this paper, Holstein bulls have been artificially inseminated with their offspring, and their offspring have been compared with the standard model of the breed. As a result, based on the performance of bull daughters, it is possible to create productive herds for the farm.